Dynamic Model Analysis of Kartini Beach Development Strategy Using Causal Loop Diagram (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2025)
Tourism development is a systematic effort to increase the attractiveness of a tourist destination through various strategies and programs. Tourism development faces multiple challenges that must be overcome to ensure sustainable growth and provide maximum benefits to local communities and tourists. Kartini Beach is one of the tourist attractions that has experienced various challenges in its development. The dynamic model approach is expected to be able to analyze the existing conditions in the management of Kartini Beach so that it can be used as a basis for compiling a strategy for developing Kartini Beach Rembang in the future. The model consists of four causal loops, three of which are positive-positive loops (reinforcement) and one negative-positive loop (balancing). A positive causal loop shows a relationship where an increase in one variable leads to an increase in another. Examples include facility development leading to higher taxes and regional income, as well as improved security, boosting tourist visits. The negative loop, such as increased traders generating waste, reduces overall visitor comfort. In the cause-and-effect table, five key strategic factors influencing the development of Pantai Kartini are identified: security, traders, visitors, facilities, and comfort. Security is influenced by the quality of facilities and services like parking, while traders and visitors impact local revenue and environmental cleanliness. Well-maintained facilities play a crucial role in improving the branding and overall comfort of the tourist site. Ultimately, comfort is determined by effective management of cleanliness, safety, and environmental conditions.